Mesenchymal stem cells reversibly de-differentiate myofibroblasts to fibroblast-like cells by inhibiting the TGF-β-SMAD2/3 pathway - Ruohao Xu; Miao Wu; Yawen Wang; Chao Li; Lingji Zeng; Yulian Wang; Maozhi Xiao; Xiaomei Chen; Suxia Geng; Peilong Lai; Xin Du; Jianyu Weng (Molecular Medicine, 2023)
Abstract Background Myofibroblasts (MFB), one of the major effectors of pathologic fibrosis, mainly derived from the activation of fibroblast to myofibroblast transition (FMT). Although MFBs were historically considered terminally differentiated cells, their potential for de-differentiation was recently recognized and implied with therapeutic value in treating fibrotic diseases, for instance, idiopathic pulmonary fibrosis (IPF) and post allogeneic hematopoietic stem cell transplantation bronchiolitis obliterans (BO). During the past decade, several methods were reported to block or reverse MFB differentiation, among which mesenchymal stem cells (MSC) have demonstrated potential but undetermined therapeutic values. However, the MSC-mediated regulation of FMT and underlying mechanisms remained largely undefined. Method By identifying TGF-β1 hypertension as the pivotal landmark during the pro-fibrotic FMT, TGF-β1-induced MFB and MSC co-culture models were established and utilized to investigate regulations by MSC on FMT in vitro. Methods including RNA sequencing (RNA-seq), Western blot, qPCR and flow cytometry were used. Result Our data revealed that TGF-β1 readily induced invasive signatures identified in fibrotic tissues and initiated MFB differentiation in normal FB. MSC reversibly de-differentiated MFB into a group of FB-like cells by selectively inhibiting the TGF-β-SMAD2/3 signaling. Importantly, these proliferation-boosted FB-like cells remained sensitive to TGF-β1 and could be re-induced into MFB. Conclusion Our findings highlighted the reversibility of MSC-mediated de-differentiation of MFB through TGF-β-SMAD2/3 signaling, which may explain MSC's inconsistent clinical efficacies in treating BO and other fibrotic diseases. These de-differentiated FB-like cells are still sensitive to TGF-β1 and may further deteriorate MFB phenotypes unless the pro-fibrotic microenvironment is corrected.